A teoria da criação do conhecimento organizacional relacionada à elaboração de relatórios de sustentabilidade empresarial: um estudo exploratório em uma empresa geradora de energia - Dihl, Winicyus (2013)
The main objective of this work is to analyse how Nonaka and Takeuchi‟s Theory of organizational knowledge creation (1997;2008) is related to writing a sustainability report under GRI regulations, in a big company of electrical power generation. The Theory previously mentioned was used as book reference, it is made up of different types of knowledge, ways of knowledge conversation, knowledge spiral, Ba – knowledge creation room, enabling conditions of organizational knowledge creation and five phases of organizational knowledge creation standard. Among the book reference taken in this paper is the five stages of sustainability report writing according to the Global Reporting Initiative (GRI). The survey was taken through three different ways, being two of them surveys with open questions and a questionnaire with questions following Likert guidelines. Based on the data collected and their analysis was possible to state that the business sustainability reporting in the company in focus goes through the creation, decoding and knowledge transference processes due to the use of explicit and tactic knowledge, in which The conversion method occurrence was identified as being connected with the knowledge creation room (Ba), sustained by specific enabling conditions, following the standard of five stages in organizational knowledge creation. Thus, the conclusion reached was that all aspects related to Organizational Knowledge Creation, elicited in the book reference, include the five stages (preparing, connecting, defining, monitoring and reporting) of business sustainability reporting according to the GRI guidelines.